Efeito do gel de doxiciclina a 10% na calvária de ratas osteoporóticas: estudo microtomográfico - Gomes, Guilherme Menali (2019)
Progress in the surgical and dental rehabilitation area has enabled the use of optimizing agents of the tissue repair process even under systemic influences. Osteoporosis is considered a public health disease. More prevalent with advancing age and in postmenopausal periods interferes with the bone repair mechanism, leading to low mineral density. Doxycycline, a product with antibiotic and antiinflammatory properties, has relevant functions on the bone tissue and becomes a useful resource to be analyzed in the repair of critical bone defects in situations of metabolic disorders, such as osteoporosis. The objective of this study was to analyze the effect of 10% doxycycline gel on bone regeneration of critical size defects in calvaria of ovariectomized rats. Sixty-eight Wistar rats were used, of which 45 were ovarectomized (OVX) and 15 sham-ovarectomized (positive control). Euthanasia, after 8 weeks, were 4 OVX and 4 SHAM-OVX rats for microtomographic characterization of osteoporosis in the femur. The remaining animals were submitted to surgery to create a critical bone defect in the calvaria using a 6mm diameter trephine drill. Subsequently, the 60 animals were divided into 4 groups (n = 15): 1 - SHAM (fictive surgery of ovariectomy and defect filled by blood clot); 2 - OVX-CS (blood clot); 3 - OVX-DOX (10% Doxycycline gel) and OVX-AUT (autogenous bone). The animals were divided into 4 groups with 5 animals / period. After 4, 8 and 12 weeks of surgery, they were euthanized and submitted to microtomographic analysis. The results were submitted to statistical analysis with significance level of 5% (Shapiro-Wilk test, followed by Tukey and Anova test). The microtomographic analysis showed higher bone volume (BV), percentage of bone volume in relation to tissue volume (BV / TV) for the OVX-AUT group with statistical differences for the other groups. There were no significant differences between the OVX-DOX, SHAM and OVX-CS groups. It was concluded that the 10% doxycycline gel did not present significant statistical results in its performance as biomaterial to fill critical bone defects of calvaria in rats female with bone metabolism altered by osteoporosis, even that was verified differences among groups and among the periods to trabecular thickness (Tb.Th) and to trabecular separation (Tb.Sp).